THE INFLUENCE OF CONFUCIANISM ON DENG XIAOPING’S REFORMATION & XI JINPING’S LEGITIMACY - Muhammad Aiman Nasuha Azari; Suseela Devi Chandran; Farhatul Mustamirrah Mahamad Aziz (Journal of Islamic, Social, Economics and Development, 2022)
This article examines the influence of an ancient Chinese philosophy, Confucianism on the leaders of China particularly Deng Xiaoping and Xi Jinping. In relation to this matter, these two Chinese leaders have been regarded as the transformational leaders of China. In this context, Deng Xiaoping is well known for his huge reputation of Chinese reformation agenda. Deng Xiaoping’s historical success has placed the current Paramount Leader of China, Xi Jinping to highly honour Deng Xiaoping’s success in transforming China. Xi Jinping clearly realises that it is essential for him to construct his own legitimacy compared to Deng Xiaoping. Therefore, this article is divided into three parts: The first part discusses the influence of Confucianism on Deng Xiaoping’s reformation while the second part of this article further explains the embracement of Confucianism by Xi Jinping in creating his own legitimacy. For the last part, this article concludes by indicating that Confucianism plays a highly significant role in Deng Xiaoping’s reformation and Xi Jinping’s legitimacy. This article is based on qualitative methodology using document analysis of various articles and journals. This method was adopted to integrate the difference components of concepts related to Confucianism and the influence of Confucianism on Deng Xiaoping and Xi Jinping.